The PAT randomised clinical trial: total knee arthroplasty versus patellofemoral arthroplasty in patients with severe arthritis of the patellofemoral joint - Joseph, M; Achten, J; Parsons, N; Costa, M (British Editorial Society of Bone and Joint Surgery, 2020)
Aim: A pragmatic, single centre, double-blind randomized clinical trial was conducted in a National Health Service teaching hospital to evaluate whether there is a difference in functional knee scores, quality of life outcome assessments and complications at one year post intervention between total knee arthroplasty (TKA) and patellofemoral arthroplasty (PFA) in patients with severe isolated patellofemoral arthritis. Patients and Methods: This parallel, two-arm, superiority trial was powered at 80%, involving 64 patients with severe isolated patellofemoral arthritis. The primary outcome measure was the functional section of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score at 12 months. Secondary outcomes were the full 24-item WOMAC, Oxford Knee Score (OKS), American Knee Society Score (AKSS), EQ-5D quality of life score, UCLA Physical Activity Rating Scale and complication rates collected at 3, 6 and 12 months. For longer term follow-up OKS, EQ-5D and self-reported satisfaction score were collected at 24 and 60 months. Results: Among 64 patients who were randomized, five patients did not receive the allocated intervention, three withdrew and one declined the intervention. There were no statistically significant differences in the patients’ WOMAC function score at 12 months adjusted mean difference, -1.2 [95% CI, -9.2 to 6.8]; P=0.77. There were no clinically significant differences in the secondary outcomes. Complication rates were comparable (superficial surgical site infections, four in the PFA group vs five in the TKA group). There were no statistically significant differences in the patients’ OKS score at 24 and 60 months or self-reported satisfaction score or pain free years. Conclusions: Among patients with severe isolated patellofemoral arthritis, this study found no difference in functional outcome at 12 months and long mid-term in the use of PFA compared to TKA. The findings support the use of PFA as an alternative to TKA in the treatment of severe isolated patellofemoral arthritis.